The version of STR stated in physics textbooks is incorrect, since it follows from it that radio engineering should not exist - Antonov, Alexander Alexandrovich (European Journal of Applied Sciences, 2022)
The article explains that, since the principle of light speed non-exceedance in the version of the special theory of relativity (STR) presented in physics textbooks implies physical unreality of any imaginary numbers, then according to this version of the STR imaginary impedance of capacitors and inductors in radio engineering should also be physically unreal. Thus, resonance should not exist in linear electric circuits and creation of filters should be impossible. Consequently, this should make existence of the whole radio technology impossible. However, since radio engineering exists, the generally accepted version of the STR presented in physics textbooks for study should be recognized as incorrect.